2013
DOI: 10.1021/jp408440z
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Nuclear Polarization of 17O: Direct Polarization

Abstract: Dynamic nuclear polarization of 17O was studied using four different polarizing agents – the biradical TOTAPOL, and the monoradicals trityl and SA-BDPA, as well as a mixture of the latter two. Field profiles, DNP mechanisms and enhancements were measured to better understand and optimize directly polarizing this low-gamma quadrupolar nucleus using both mono- and bi-radical polarizing agents. Enhancements were recorded < 88 K and were > 100 using the trityl (OX063) radical and < 10 with the other polarizing age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 143 publications
4
93
0
Order By: Relevance
“…Additionally, direct DNP could be preferred for quadrupolar nuclei because it is often challenging to efficiently transfer 1 H magnetization to quadrupolar spins. 17 O labeled water at 5 T with trityl radical as the PA. 15 They also showed that mixtures of BDPA and trityl monoradicals were efficient PA for CE direct DNP of spins with Larmor frequencies below that of 13 C. 16 They obtained 13 C direct CE DNP enhancements of 620 at a magnetic field of 5 T, which corresponds to ca. 25% of the theoretical maximum 13 C direct DNP enhancement of 2620.…”
Section: Dnpmentioning
confidence: 99%
“…Additionally, direct DNP could be preferred for quadrupolar nuclei because it is often challenging to efficiently transfer 1 H magnetization to quadrupolar spins. 17 O labeled water at 5 T with trityl radical as the PA. 15 They also showed that mixtures of BDPA and trityl monoradicals were efficient PA for CE direct DNP of spins with Larmor frequencies below that of 13 C. 16 They obtained 13 C direct CE DNP enhancements of 620 at a magnetic field of 5 T, which corresponds to ca. 25% of the theoretical maximum 13 C direct DNP enhancement of 2620.…”
Section: Dnpmentioning
confidence: 99%
“…Promising developments have been made in recent years toward efficient direct DNP using trityl radicals. 28,29 It should be noted that the DNP transfer step is most efficient at low temperatures, and therefore, most experiments are presently carried out at temperatures not exceeding 110 K.…”
Section: Dnp Ssnmrmentioning
confidence: 99%
“…These properties make the use of DNP particularly attractive. 29,40 Indeed, in spite of all of these shortcomings, DNP-enhanced NMR spectroscopy has enabled the measurement of 17 O NMR spectra at natural isotopic abundance. 41,42 For example, DNP-enhanced, natural abundance, 17 O{ 1 H} MAS spectra of inorganic hydroxides were recently obtained in our laboratory, enabling the swift measurements of O−H distances and heteronuclear correlation (HETCOR) spectra.…”
Section: Dnp Ssnmr Of Challenging Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…However, exogenous monoradicals can also be used and show promise for various applications such as direct hyperpolarization of low-γ nuclei [6] and very high magnetic field strengths (414 T) [7], the latter being a result of an observed Overhauser effect in insulating solids -a highly interesting result that escaped prediction. Furthermore, access to both lower [8] and higher [9] temperatures than $ 100 K are currently desired and are under development, although these conditions are very much in their infancy and much progress still needs to be made.…”
mentioning
confidence: 99%